Pertanggungjawaban Pidana Pelaku Penyertaan Tindak Pidana Pemalsuan - Novita Anggriani Lahabu; Rafika Nur; Darmawati Darmawati (Pusat Riset dan Inovasi Nasional, 2023)
There are so many cases where the perpetrators are more than one person, which occur in our society. Often there is debate in imposing punishment on the direct makers and the indirect makers of criminal acts. To impose a sentence on a case, the judge must know which maker is directly or indirectly and bases his decision apart from the law and also considers the demands of the public prosecutor. Sometimes the perpetrators of the crime of participation are not touched at all by the law so that what they should be prosecuted by law is not even processed. The purpose of this study is to examine the criminal responsibility of the perpetrators of the crime of counterfeiting. The research conducted is normative legal research. Based on the results of the research the defendant was proven guilty of committing the crime of